Use of Guidance Material for Moving and Handling People: Barriers and Facilitators - An Experience Exchange - Lidegaard, M; Olsen, KB; Legg, SJ (Massey University)
Presentation of the research project and preliminary findings of questionnaire survey as introduction to a work shop for people interested in improving health and safety related to moving and handling people.